Interconnecting DC busses of solar/wind based power supply system - Yap, Ning Xin. (2012)
Modern day alternative energy sources come in different forms, i.e. 1) solar, 2)Wind, etc. To supply a common household/domestic load, these forms of energy first need to be brought to a common form, say, DC and then changed/distributed again depending on the load requirement. To interconnect two DC buses, they must be at the same potential level. The aim of this project is to investigate the necessary conditions for such bus interconnections to transfer max. power from the source to the load.